Analisis Karakter Streamer Mobile Legend: Bang Bang dalam Perspektif Akhlak Islami - Rifai, Alfan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
The phenomenon of Mobile Legends: Bang Bang live streaming has become a popular form of entertainment, especially among teenagers, yet the behavior of streamers during live broadcasts often displays diverse characteristics that can potentially influence the viewers' morals. This study aims to analyze the character of Mobile Legends streamers from the perspective of Islamic morals, focusing on how their behavior impacts viewers, particularly teenagers who are prone to idolizing streamers. Using qualitative methods and content analysis, this research identifies two main categories: commendable morals (akhlaq mahmudah) and disgraceful morals (akhlaq madzmumah). Streamers like Marsha Ozawa and R7 Tatsumaki exhibit commendable traits such as patience, teamwork, and self-control, while others like Pascol and Brandon Kent display negative behaviors, including using harsh language, acting impulsively, and showing ungratefulness. These streamer behaviors significantly impact viewers, with negative actions normalizing poor habits and positive actions inspiring Islamic values. This study highlights the importance of educating streamers about Islamic morals and the role of streaming platforms in creating a digital environment that is both educational and ethical.